Antibiotic residues in honey: a public health issue (Research, Society and Development, 2020)
Honey has numerous uses and composes formulations of many food, pharmaceutical, and cosmetic products due to its chemical, biological, and sensorial characteristics. In recent years, several reports and scientific articles claim the contamination of honey by antibiotics, a fact that is a public health problem since the ingestion of them can cause several side effects. In this sense, the purpose of this work was to carry out a literature review in international circulation databases about the contamination of honey by antibiotics in the last 10 years. It is observed in the literature that several quality control methods for evaluating this product have been developed, with the main objective of detecting trace concentrations of these compounds. In this context, the chromatographic techniques, rapid tests, immunoassays, and the use of emerging technologies that are considered sustainable for sample preparation stand out. When these methods are applied to honey samples, it is clear that the contamination of honeys by antibiotic residues has been growing every year, making it evident that programs for continuous monitoring of these residues in honeys are conducted. Also, not only has the amount of antibiotics increased, but also the diversity of assets being used. Regarding the residues present, the main antibiotics found in the evaluated samples belong to the class of tetracyclines, sulfonamides, aminoglycosides, macrolides, and amphenicols. However, few countries report maximum residue limits (MRL) allowed for these substances in honey, and in Brazil, as well as in the European Union, no MRL has been established for antibiotics in this product so far, which indicates that it is extremely important that MRL be adopted to ensure food safety for consumers.